Chemopreventive properties of 3,3'-diindolylmethane: From experimental to clinical studies. A review - Andrei V. Vlasov; Oksana V. Yakushevskaya (IP Berlin A.V., 2024)
The basis for the prevention of cancer is the correction of initial epigenetic disorders in the cell, i.e. implementation of pathological genome reversion. Convincing evidence has accumulated to support the potential antitumor activity of compounds derived from cruciferous vegetables of the genus Brassicaceae. Indole-3-carbinol and 3,3'-diindolylmethane (DIM) have been investigated for their use as chemopreventive agents. DIM is formed in the acidic environment of the stomach as a result of dimerization of indole-3-carbinol monomers. Currently, it is impossible to identify a specific vector of influence of DIM at the molecular level. In this review, we summarize the pleiotropic effects of DIM aimed at correcting reversible epigenetic changes in tumor cells. Emphasis will be placed on the major cellular and molecular events that are effectively modulated by DIM. The main profile of DIM competencies concerns the management of intracellular signal transmission and correction of initial molecular genetic changes at the level of key participants in signaling pathways (NF-κB/Wnt/Akt/mTOR) leading to the development of cancer. The ability of DIM to differentially modulate tumor cell apoptosis has been observed in preclinical studies. It has been suggested that using DIM it is possible to increase the effectiveness of chemotherapeutic compounds with different molecular targets, thereby increasing chemosensitization. DIM has entered phase III clinical trials, with preliminary results confirming its promise both as a stand-alone drug and in combination with other components of anticancer therapy. Establishing the range of epigenetic control of DIM molecular and genetic changes in various cancers will allow optimization of therapeutic epigenetics approaches.